Respiratory function in vocal soloists, opera singers and wind instrument musicians - Ksinopoulou, Helen; Hatzoglou, Chryssa; Daniil, Zoe; Gourgoulianis, Konstantinos; Karetsi, Helen (La Medicina del Lavoro, 2016)
Introduction: Current studies have not yet reached a definitive conclusion on the effects of singing and playing wind instruments professionally on an individual’s respiratory function. Objective: The purpose of this study was to investigate the respiratory function of wind instrument players and opera singers in comparison with a group of healthy individuals. Methods: The experimental group comprised 45 men and 35 women, 58 opera singers and vocal soloists in total and 22 wind instruments players. Eighty controls were all non-smokers, healthy individuals, matched for age and sex. Spirometry was performed with a dry spirometer, according to the American Thoracic Society recommendations. Results: The mean age of the experimental group was 47.9 (15.5) years for men and 46.6 (16.8) for women. Experimental group and controls differed (p